Tuning Electronic Properties of GaSe/Silicane Van der Waals Heterostructure by External Electric Field and Strain: A First-Principle Study - Gang Xu; Hao Lei (Advances in Condensed Matter Physics)
The electronic structure of GaSe/silicane (GaSe/SiH) van der Waals (vdW) heterostructure in response to a vertical electric field and strain was studied via first-principle calculations. The heterostructure had indirect band gap characteristics in the range [−1.0, −0.4] V/Å and direct band gap features in the range [−0.3, 0.2] V/Å. Furthermore, a type-II to type-I band alignment transition appeared at −0.7 and −0.3 V/Å. Additionally, the GaSe/SiH vdW heterostructure had a type-II band alignment under strain, but an indirect to direct band gap semiconductor transition occurred at −3%. These results indicated that the GaSe/SiH vdW heterostructure may have applications in novel nanoelectronic and optoelectronic devices.